Personalized Medicine in Malignant Melanoma: Towards Patient Tailored Treatment - Helgadottir, Hildur; Rocha Trocoli Drakensjö, Iara; Girnita, Ada (Frontiers in Oncology, 2018)
Despite enormous international efforts, skin melanoma is still a major clinical challenge. Melanoma takes a top place amongst the most common cancer types and it has one of the most rapidly increasing incidences in many countries around the world. Until recent years, there have been limited options for effective systemic treatment of disseminated melanoma. However, lately we have experienced a rapid advancement in the understanding of the biology and molecular background of the disease. This has led to new molecular classifications and the development of more effective targeted therapies adapted to distinct melanoma subtypes. Not only are these treatments more effective but they can be rationally prescribed to the patients standing to benefit. As such, melanoma management has now become one of the most developed for personalized medicine. The aim of the present paper is to summarize the current knowledge on melanoma molecular classification, predictive markers, combination therapies as well as emerging new treatments.